Cisplatin Ototoxicity, Increased DPOAE Amplitudes, and Magnesium Deficiency - Cevette, Michael J.; Drew, Danielle; Webb, Teresa M.; Marion, Mitchell S. (Journal of the American Academy of Audiology, 2000)
Outer hair cell (OHC) metabolism is blocked by cisplatin. Concurrent changes in the renal handling of magnesium occur because of the damage cisplatin causes to the renal proximal tubule cells within the thick ascending loop of Henle. Although there is no evidence of cisplatin within the OHCs, there are significant levels of intracellular calcium, the antagonist to magnesium at the cell membrane. The OHC motile response is dependent on intracellular calcium. When the calcium current is suppressed by an antagonist, the extracellular OHC microphonic potential decreases. Magnesium deficiency is known to produce hyperexcitabililty within the central nervous system, including fatal audiogenic seizures. In addition, increases in the amplitude of the auditory brainstem response wave V occur with aminoglycoside therapy and magnesium deficiency. This paper illustrates the amplitude growth of distortion product otoacoustic emissions in two patients treated with cisplatin and explores the possible underlying reasons why this may be related to magnesium metabolism.Abbreviations: DPOAEs = distortion product otoacoustic emissions, OAEs = otoacoustic emissions, OHC = outer hair cell, TEOAEs = transient otoacoustic emissions
Keywords: Cisplatin chemotherapy; distortion product otoacoustic emissions; magnesium deficiency; outer hair cells; transient evoked otoacoustic emissions